Occurrence, pathogens and risk factors for subclinical mastitis in dairy goats - Machado, G. P.; Guimaraes, F. F. [UNESP]; Menozzi, B. D. [UNESP]; Salina, A. [UNESP]; Possebon, F. S. [UNESP]; Langoni, H. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2018)
Milk samples from 257 goats and 513 half udders of 10 dairy goat farms were analyzed by microbiological culture, to evaluate the sanitary management, and epidemiological questionnaire results. Multivariate analysis of risk factors for subclinical mastitis in goats, with the adjusted Odds Ratio for subclinical mastitis was performed. The prevalence of subclinical mastitis in goats by microbiological culture was 43.6%, and clinical mastitis was 5.84%. From 178 positive teats by microbiological culture, the most prevalent pathogens were coagulase-negative staphylococci - CNS (70%), S. aureus (13.5%), S. intermedius (7.9%), and Enterobacteriaceae (4%). The risk factors analysis revealed significant association between the disease and the flock size (OR = 3.33; P = 0.0268), and the farm was a confounding factor, being kept in the final statistical model. Despite the non-identification of all the factors associated with subclinical mastitis in herds and the existence of confounding factors that hinder statistical analyzes, the study of risk factors is important for the improvement of disease control and prevention programs in dairy goat, and it can be used as a tool in the reduction of environmental and contagious pathogens such as staphylococci that were the most identified pathogens causing caprine mastitis in the study.
Keywords: goat mastitis; milk quality; epidemiology; risk factors